Rehmanniae Radix Preparata ameliorates behavioral deficits and hippocampal neurodevelopmental abnormalities in ADHD rat model - Sun, Ruxin; Yuan, Haixia; Wang, Jing; Zhu, Kanglin; Xiong, Yu; Zheng, Yabei; Ni, Xinqiang; Huang, Min (Frontiers in Neuroscience, 2024)
Abnormal neurodevelopment of the hippocampus, particularly in the dentate gyrus region, may be a key mechanism of attention-deficit/hyperactivity disorder (ADHD). In this study, we investigate the effect of the most commonly used Chinese herb for the treatment of ADHD, Rehmanniae Radix Preparata (RRP), on behaviour and hippocampal neurodevelopment in spontaneously hypertensive rats (SHR). Behavior tests, including Morris water maze (MWM) test, open field test (OFT) and elevated plus maze (EPM) test were performed to assess the effect of RRP on hyperactive and impulsive behavior. Hippocampal neurodevelopment was characterized by transmission electron microscopy, immunofluorescence, Golgi staining and Nissl staining approaches. Regulatory proteins such as Trkb, CDK5, FGF2/FGFR1 were examined by Western blot analysis. Results revealed that RRP could effectively control the impulsive and spontaneous behavior and improve the spatial learning and memory ability. RRP significantly reduced neuronal loss and increased the number of hippocampal stem cells, and promoted synaptic plasticity. Additionally, FGF/FGFR signalling was upregulated after treatment with RRP. Taken together, RRP can effectively reduce impulsive and spontaneous behavior and ameliorate hippocampal neurodevelopmental abnormalities in ADHD rat model.